Parallel visualization approach of a 3D heart model - Malekpour, A.; Ling, T.C.; Lim, W.C. (2008)
In recent years, the employment of IEEE 802.11 radio signals for location determination in an indoor environment has drawn great attention. The basis of this technique is that the location of an object is estimated using an estimation algorithm and the radio frequency (RF) fingerprint database as a reference. The main target of this paper is to find an optimum strategy for the construction of the RF map and a decent estimation algorithm. By obtaining statistical data from several signal strength measurements, we investigate and identify three influential factors on the RSSI behavior. With this knowledge, we propose improvement to the existing deterministic algorithm. An algorithm for detection of and dealing with the aliasing problem is also suggested Test results show that our proposed combinational deterministic method and the anti aliasing technique improves the system performance by up to 33% compared to other deterministic method using single scalar values.